Developing Reading Skills Picture Cards as a Learning Tool for First Grade Students at State Elementary School Number 107423 Tanjung Garbus Pagar Merbau District Deli Serdang 2023-2-24 - Rosliana Rosliana; Sutikno Sutikno (PT Inovasi Pratama Internasional, 2024)
The use of the game method will be more effective if supported by the media as a learning aid in helping grade 1 elementary school students develop reading competence. The formulation of this research problem is: How is the development of reading competence through learning media picture cards of grade I students of SD Negeri Number 107423 Tanjung Garbus, Pagar Merbau District, Deli Serdang Regency for the 2023-2024 Academic Year?